Budaya Sekolah di Sekolah Menengah Kejuruan (SMK) Negeri 2 Padang - Utari Octaviani; Ahmad Sabandi; Hanif Al Kadri; Nurhizrah Gistituati (Journal of Educational Administration and Leadership, 2020)
The background of this study is the result of the author’s observations which indicate that there is a lack of strong school culture in the Vocational High School 2 Padang. This research is a quantitative descriptive type with the aim of seeing how strong the school culture is as values, namely honesty, cooperation, trust, and responsibility. The population of this research is 100 teachers os SMK Negeri 2 Padang. Determining the number of samples in this study using the Slovin formula at an error rate of 10% of the total population and sampling using the proportionate stratified random sampling technique to produce 51 people. The research instrumen used a questionnaire (paper) with a Likert scale, amounting to 40 statements. The data collected is then processed and the average score (mean) and the respondent’s level of achievement (TCR) are sought. The results of data processing show that school culture seen from the aspect of honesty gets an average score of 4,58 (TCR 91,5%), cooperation gets an average score of 4,44 (TCR 88,8%), trust gets an average score 4,45 (TCR 89,1%), and responsibility got an average score of 4,25 (TCR 84,9%). Overall, the school culture in Vocational High School 2 Padang obtaines an average score of 4,43 (TCR 88,6%).